Atypical manifestation of cutaneous paracoccidioidomycosis in pediatrics (Actualizaciones en Sida e Infectología, 2025)
Paracoccidioidomycosis (PCM) is an endemic systemic mycosis, caused by the species P. braziliensis and P. lutzii of the genus Paracoccidioides, exclusive to Latin America and predominant in areas with a humid subtropical climate. Primary infection may be asymptomatic or cause mild respiratory symptoms that may be self-limiting or progress to disease, whether pulmonary or disseminated, with eventual skin involvement. Diagnosis is made by direct examination, culture, histopathology and serology. The treatment of choice is Itraconazole. We report the case of a 13-year-old male patient diagnosed with PCM with skin involvement as the only clinical manifestation.
Keywords: Paracoccidioides braziliensis; Paracoccidioidomycosis; Endemic disease; Dermatology